Resurgence of post-crisis neoliberalism: labor law reform and the return to "business as usual" in Lithuania. Issue 4 (2nd October 2019) - Juska, Arunas; Lazutka, Romas
ABSTRACT: The economic crisis of 2008–2010 revealed the extreme vulnerability of Lithuania to global financial shocks. However, instead of reforming Lithuanian capitalism, the domestic political and business elites chose to write off the enormous social and economic costs incurred during the 2008–2010 crisis as an expense of continuing doing business in a way that was typical to the pre-crisis, booming years of 'the Baltic tigers' (2000–2007), i.e., relying on the unstable and inequitable growth model based on foreign capital inflows and remittances, suppressing and keeping wages and taxes on capital low and exporting cheap-skilled labour to the core EU countries. We illustrate this return to business as usual in Lithuania by analyzing the political process of contestation and eventual consolidation of neo-liberal consensus among domestic political actors that resulted in the passage of the new Labour Code enabling creation of 'flexible' labor markets. Social and political implications of the resurgent neoliberal hegemony in post-crisis Lithuania are discussed.